The use of abciximab associated with primary angioplasty for treating acute myocardial infarction - Brito,Manuel Lisandro Hernández (2002)
OBJECTIVE: To assess the benefit resulting from the use of abciximab associated with primary angioplasty. The following parameters were analyzed in-hospital, at 30 days, and 6 months: (a) flow in the culprit artery; (b) ventricular function; (c) combined outcome of death, acute myocardial infarction, and aditional revascularization. METHODS: From November 1997 to June 1999, a longitudinal nonrandomized study with historical data of 137 patients with acute myocardial infarction within the first 12 hours. Patients undergoing primary angioplasty and were divided into 2 groups: those receiving (A) abciximab (26) or (B) conventional therapy (111). TIMI flow and regional ventricular function estimated by the standard deviation (SD)/chordis index were analyzed. RESULTS: At the end of angioplasty, TIMI 3 flow was observed in 76.9% and 83.8% of the patients in groups A and B, respectively (P=0.58). In the reevaluation, patients with TIMI flow <3 showed a 100% improvement in group A and a 33% in group B (P<0.0001). A significant improvement (P<0.0001) in regional ventricular function, by SD/chordis index, occurred in each group; no significant difference between groups however, was observed (29.9% x 20.2%; P=0.58). A nonsignificant reduction in the combined outcome in the in-hospital phase (3.85% A x 9.0% B; P=0.34) and on the 30th day (4.0% x 12.0%; P=0.22) was observed in group A. CONCLUSION: Abciximab improved blood flow. Primary angioplasty improved regional ventricular function independent of antithrombotic therapy. Abciximab showed a trend toward reducing the combined outcome in the in-hospital phase and on the 30th day.